Study on the mechanism of black Chinese wolfberry (Lycium ruthenicum Murr.) polyphenols relieving male urogenital damage caused by benzophenone-3 based on network pharmacology - SUN Jiahe; DIAO Hong; YANG Haixin; CHEN Xuying; WANG Haowen; GAO Yanrong; XU Haiming; LI Hongmei (Guangxi Yike Daxue xuebao)
Objective To investigate the effects of the polyphenols extracted from Lycium ruthenicum Murr. (L. ruthenicum) on male urogenital damage caused by benzophenone-3 (BP-3) and its mechanism. Methods The male urogenital toxicity targets of BP-3 and the pharmacological targets of L. ruthenicum polyphenols were screened by the CTD database, Swiss Target Prediction and TargetNet databases, respectively. The intersecting targets of BP-3 and L. ruthenicum polyphenols were obtained by the Venny 2.1.0 tool. The targets were entered into the STRING database to construct a protein interaction network. GO biological process enrichment analysis and KEGG metabolic pathway enrichment analysis were performed in R language environment. Cytoscape 3.8.2 software was used to construct the polyphenol-common target-pathway network of L. ruthenicum. AutoDock Vina 1.1.2 software was used to molecularly dock the above targets with L. ruthenicum and BP-3, respectively. Results A total of 56 potential targets of the BP-3 male urogenital system, 296 potential pharmacological targets of L. ruthenicum polyphenols, and 14 intersecting targets were screened out. The pharmacokinetic analysis showed that the components of L. ruthenicum polyphenols-coumaric acid and caffeic acid had better drug-like properties and stronger intestinal absorption. The results of GO and KEGG enrichment analyses suggested that BP-3 and L. ruthenicum polyphenols could act on the male urogenital system. The results of the common target-pathway network analyses showed that molecules such as PIK3R1 and TP53 might play a crucial role in L. ruthenicum polyphenols alleviating BP-3-induced male urogenital injury. The molecular docking results showed that BP-3 and L. ruthenicum polyphenols could bind to the amino acids near the active sites of PIK3R1, TP53, ESR1, PTGS2, and ESR2 through chemical bonding forms such as hydrogen bonding, and both had strong binding energy with target proteins. Conclusion The L. ruthenicum polyphenols can alleviate BP-3-induced male urogenital damage to a certain extent, and the target molecules such as PIK3R1, TP53, ESR1, PTGS2, and ESR2 may mediate the above antagonistic effects.